Word of Mouth : Gossip and American Poetry - Bennett, Chad, 1976- (Book collections on Project MUSE., 2018)
"Word of Mouth brings together the insights of queer and lyric theory to tell the story of how gossip modeled forms of sociality and voice that poets experimented with over the course of the twentieth century. Through a set of case studies of culturally diverse American poets--Gertrude Stein, Langston Hughes, Frank O'Hara, James Merrill, and others--who absorbed and contended with the loose talk that swirled about them and their work, the book argues that gossip became a vehicle for the performance of alternative sexualities and concomitant meditations on alternative modes of poetic practice. At the heart of this argument is a queer revaluation of modern lyric poetry. Attending to gossip's key role in modern and contemporary poetry enables a recognition of the unpredictable ways that conventional understandings of the modern lyric poem--as, for example, an utterance smudging the lines between private and public, knowing and unknowing, intimacy and strangeness--have been shaped by, and afforded a uniquely suitable space for, the expression of queer sensibilities. More than simply mapping a curious poetic mode, then, Word of Mouth contributes a crucial, and largely neglected, queer perspective to current lyric studies and its renewed scholarly debate over the practices and forms of lyric poetry. The book presents new and instructive queer contexts for understanding the influential formal achievements of Stein, Hughes, O'Hara, and Merrill, and uncovers the unexpected ways that the history of the modern lyric intertwines with histories of sexuality"--